HUBUNGAN ANTARA RELIGIUSITAS DENGAN MORALITAS PADA REMAJA DI MADRASAH ALIYAH (MA) - Iredho Fani Reza (Universitas Ahmad Dahlan, 2013)
AbstractAdolescents who exhibit behaviors according to the prevailing norms and values, the teen said to have morality. While teens who show behavior contrary to the prevailing norms and values, then the teenager is said to commit immoral acts. The results of previous studies, concluded that, individuals need a controller in thinking, behaving , acting , namely religion or religiosity. Religiosity can affect every aspect of an individual’s life, bothpsychologically and physically. This study aims to examine the relationship between religiosity and morality in adolescents at Madrasah Aliyah. This type of research uses a quantitative approach to the type of correlational research. The population numbered 93 students of Madrasah Aliyah 2012- 2013 school year. The sampling technique using simple random technique,the sample in the study totaled 63 students. Analyzed using product moment. The results of this study showed a correlation coefficient ( r) of 0.775 with a significance ( p ) of 0.000, where p < 0.01. Based on data analysis, the conclusions drawn from this study is that there was a significant relationship between religiosity and morality teen Madrasah Aliyah Boarding Schoolsin the city of Palembang.Keywords : Morality, Religiosity.